Understanding Events 2008
DOI: 10.1093/acprof:oso/9780195188370.003.0023
|View full text |Cite
|
Sign up to set email alerts
|

20 Dynamics and the Perception of Causal Events

Abstract: We use our knowledge of causal relationships to imagine possible events. We also use these relationships to look deep into the past and infer events that were not witnessed or to infer what can not be directly seen in the present. Knowledge of causal relationships allows us to go beyond the here and now. This chapter introduces a new theoretical framework for how this very basic concept might be mentally represented. It proposes an epistemological theory of causation — that is, a theory that specifies the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…The impression of causality in simple mechanical events is built on spatial and temporal elements (e.g., Blakemore et al, 2003; Buehner and Humphreys, 2010; Fonlupt, 2003; Fugelsang et al, 2005; Guski and Troje, 2003; Roser et al, 2005; Scholl and Tremoulet, 2000; Wolff, 2007, 2008; Woods et al, 2012). For example, in a mechanical event with two objects, spatial continuity and temporal contiguity increases the likelihood that a person will perceive causality (e.g., Straube and Chatterjee, 2010; Woods et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impression of causality in simple mechanical events is built on spatial and temporal elements (e.g., Blakemore et al, 2003; Buehner and Humphreys, 2010; Fonlupt, 2003; Fugelsang et al, 2005; Guski and Troje, 2003; Roser et al, 2005; Scholl and Tremoulet, 2000; Wolff, 2007, 2008; Woods et al, 2012). For example, in a mechanical event with two objects, spatial continuity and temporal contiguity increases the likelihood that a person will perceive causality (e.g., Straube and Chatterjee, 2010; Woods et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When one object—for instance, a billiard ball—moves towards another, the timing and direction of movement of both objects influences our perception of whether one object causes the other to move. This spatial and temporal information conveys a sense of forces underlying causal relationships in an event (Wolff, 2007, 2008). Contextual information, such as recent experience and prior knowledge, also influences the perception of causality (Buehner and May, 2002, 2003; Gruber et al, 1957; Powesland, 1959; Schlottmann, 1999; Shanks, 1985; Woods et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Causative events are of interest because they are complex events composed of multiple dynamic subcomponents that overlap in time and space. Several studies have looked at the way that infants, children, and adults reason about causative events (Bunger, 2006; Cohen, Rundell, Spellman & Cashon, 1999; Göksun, George, Hirsh-Pasek & Golinkoff, 2013; Leslie, 1984; Leslie & Keeble, 1987; Oakes & Cohen, 1990; Wolff, 2007, 2008) and the way that learners come to encode subcomponents of such events into different types of verbs (Behrend, 1990; Behrend, Harris & Cartwright, 1995; Bowerman, 1989; Bunger, 2006; Forbes & Farrar, 1993, 1995; Gentner, 1978; Gropen, Pinker, Hollander & Goldberg, 1991; Naigles, 1996; Papafragou & Selimis, 2010; Slobin, 1985). However, the cross-linguistic description of causative events has been the topic of only a few studies – and those mostly in adults (Klettke & Wolff, 2003; Wolff, Jeon, Klettke & Yu, 2010; Wolff, Jeon & Yu, 2009; Wolff & Ventura, 2009; but cf.…”
mentioning
confidence: 99%
“…The upshot of these experiments is that the kinematics of a movement contains information that is sufficient for the identification of the underlying dynamic force patterns, that is velocities and accelerations (Runesson, 1994). Further psychological evidence [Wolff (2007[Wolff ( , 2008, Wolff and Shepard (2013), Wolff and Thorstad (2017)] supports that people can directly perceive the forces that control different kinds of motion.…”
Section: Causal Reasoning With Forces Human Reasoning About Forcesmentioning
confidence: 99%
“…Another central aspect is that the forces of an agent are not the only elements involved in human causal judgements, but counterforces of various kinds (forces exerted by a patient or contextual forces such as gravitation) are also taken into account. This aspect is included in Talmy's (1988) 'force dynamics' and is further developed in Wolff's (2007Wolff's ( , 2008Wolff's ( , 2012 'dynamics model'. Wolff (2007) has shown that adults can combine different kinds of forces in their reasoning.…”
Section: A Cognitive Approach To Causationmentioning
confidence: 99%